Development of an Efficient Steel Beam Section for Modular Construction Based on Six-Sigma - Tae-Hyu Ha; Bong-Ho Cho; Hongjin Kim; Dae-Jin Kim (Advances in Materials Science and Engineering)
This study presents a systematic approach for the development of an efficient steel beam section for modular construction based on Six-Sigma. Although the Six-Sigma is frequently implemented in manufacturing and other service industries, it is a relatively new concept in the area of building design and construction. As a first step in this approach, market studies and surveys are conducted to obtain the opinions of potential customers. Then the opinions of customers are converted into quality characteristics for the steel beam using the quality function deployment methodology. A steel hollow flanged channel is chosen as the main modular beam shape, and the design concept is derived and developed by applying the Pugh matrix methodology. A pilot test was performed to validate the effectiveness of the developed beam section. The results indicated that the developed channel beam section showed excellent performance and retained high accuracy in fabrication, thus resulting in a significant reduction of steel consumption.